Productivity in mass crosses of Drosophila sturtevanti: A comparative study of laboratory stocks and recently collected flies - Hosaki-Kobayashi, M. K. [UNESP]; Melara de Campos Bicudo, H. E. [UNESP] (My University, 1994)
Drosophila sturtevanti from several geographic origins were analyzed for their capacity to intercross and to yield progeny. Mass intercrosses involving laboratory stocks and recently collected strains were fertile, which suggests that the genetic differentiation among these geographically isolated populations did not affect their reproductive patterns sufficiently to lead to reproductive isolation. Analysis of the number of progeny (productivity) in intracrosses and intercrosses was informative as to the amount of variation this feature exhibits in the laboratory stocks and in the recently collected strains. Also laboratory stocks and recently collected flies shared a positive correlation in that the greater the control productivity of a strain the greater the number of its intercrosses which exhibited reduced productivity.